Ho Chi Minh’s Ideology on Religious Tolerance and The Value of This Ideology for Religious Unity in Vietnam Today - Do, Tu Duy; Nguyen, Phuong Thi Hong (Journal of Ecohumanism, 2024)
Ho Chi Minh's ideology of tolerance is a philosophical - ethical category that reflects love, respect, recognition, and protection of all human rights and basic freedoms of everyone; is respect and acceptance of the diversity and richness of political views, cultures, and religions, finding similarities in differences; is the expression of the responsibility to maintain and protect basic human rights in economic development, building political, military, and diplomatic systems to gather and unite different forces towards the goal of liberating people. Ho Chi Minh's ideology of tolerance has a broad connotation, containing many great contents, and is valuable for the practical development of all fields of social life. Within the scope of this study, we analyze the basic content of Ho Chi Minh's ideology on religious tolerance, expressed in a number of aspects, such as: Ho Chi Minh's awareness of religious freedom; Respect the beliefs, freedoms and beliefs of the people; Resolutely fight against those who tarnish the sacredness of religion; Sincerely respect the faith of religious people, affirming the moral and humanistic values ​​of religious founders; Refers to the State's responsibility towards religion. On that basis, the article summarizes some theoretical and practical values ​​of this ideology for the issue of religious unity in Vietnam today.